Bilateral Vestibular Loss - Hain, Timothy C.; Cherchi, Marcello; Yacovino, Dario A. (Seminars in Neurology, 2013)
Bilateral vestibular loss is a rare cause of visual disturbance (oscillopsia) and imbalance. When severe, the most common cause is iatrogenic-gentamicin ototoxicity. Bilateral loss is easily diagnosed at the bedside with the dynamic illegible E test. If this test is omitted, it can easily be misdiagnosed as a cerebellar syndrome. Treatment is largely supportive. Care should be taken to avoid medications that suppress vestibular function, and to encourage activity.
Keywords: vestibulopathy; ototoxicity; ataxia; oscillopsia